Epigenetic modifications as therapeutic targets in atherosclerosis: a focus on DNA methylation and non-coding RNAs - Sum, Hashum; Brewer, Alison C. (Frontiers in Cardiovascular Medicine, 2023)
Significant progress in the diagnosis and treatment of cardiovascular disease (CVD) has been made in the past decade, yet it remains a leading cause of morbidity and mortality globally, claiming an estimated 17.9 million deaths per year. Although encompassing any condition that affects the circulatory system, including thrombotic blockage, stenosis, aneurysms, blood clots and arteriosclerosis (general hardening of the arteries), the most prevalent underlying hallmark of CVD is atherosclerosis; the plaque-associated arterial thickening. Further, distinct CVD conditions have overlapping dysregulated molecular and cellular characteristics which underlie their development and progression, suggesting some common aetiology. The identification of heritable genetic mutations associated with the development of atherosclerotic vascular disease (AVD), in particular resulting from Genome Wide Association Studies (GWAS) studies has significantly improved the ability to identify individuals at risk. However, it is increasingly recognised that environmentally-acquired, epigenetic changes are key factors associated with atherosclerosis development. Increasing evidence suggests that these epigenetic changes, most notably DNA methylation and the misexpression of non-coding, microRNAs (miRNAs) are potentially both predictive and causal in AVD development. This, together with their reversible nature, makes them both useful biomarkers for disease and attractive therapeutic targets potentially to reverse AVD progression. We consider here the association of aberrant DNA methylation and dysregulated miRNA expression with the aetiology and progression of atherosclerosis, and the potential development of novel cell-based strategies to target these epigenetic changes therapeutically.